Peran Masyarakat Hukum Adat dan Perlindungan Hukum Pemerintah terhadap Pengelolaan Hutan Adat - Marshandi Pratama Uduala (Universitas Kapuas, 2026)
This study examines the role of indigenous peoples in the management of customary forests, as well as the government’s efforts to provide legal protection for indigenous peoples’ rights over communal (ulayat) forests. The research employs a normative legal method, using statutory, conceptual, and legal-sociological approaches through a literature review of primary, secondary, and tertiary legal materials. The findings indicate that indigenous peoples play an active role in managing customary forests based on customary law and local wisdom, which has proven to support both ecological and social sustainability. Legal protection provided by the government is grounded in constitutional and juridical foundations, including Constitutional Court Decision Number 35/PUU-X/2012; however, its implementation remains constrained by regulatory disharmony, reliance on regional administrative recognition, and sectoral policies that have yet to be fully integrated. This study underscores the need to strengthen a coherent national legal framework to ensure effective protection of indigenous peoples’ communal forests.